Efficiency losses through fragmentation? Scale effects in European ANS provision. Issue 4 (December 2019) - Standfuss, Thomas; Fichert, Frank; Schultz, Michael; Stratis, Petros
Fragmentation has been suspected of contributing to inefficiencies in the European Air Traffic Management (ATM) system. Heterogeneities between providers may contain multiple aspects, such as airspace structure, staff rostering, or systems used for flow management. Applying the scientific approach of data envelopment analysis, this article provides a new outlook on the relationship between airspace fragmentation and efficiency in the admittedly complex and highly dynamic environment of European ATM. We show that there are airspaces that might benefit from economies of scale, but that there is a tipping point where diseconomies of scale occur. Subsequently, the current approach of functional airspace blocks might inhere inefficiencies for some air navigation service providers.